Factors Involved in the onset of infection following bacterially contaminated platelet transfusions. (3rd October 2021) - Wilson-Nieuwenhuis, Joels; El-Mohtadi, Mohamed; Edwards, Kurtis; Whitehead, Kathryn; Dempsey-Hibbert, Nina
Abstract: Transfusion of platelet concentrates (PCs) is associated with several adverse patient reactions, the most common of which are febrile non-hemolytic transfusion reactions (FNHTRs) and transfusion-associated bacterial-infection/transfusion-associated sepsis (T-ABI/TA-S). Diagnosis of T-ABI/T-AS requires a positive blood culture (BC) result from the transfusion recipient and also a positive identification of bacterial contamination within a test aliquot of the transfused PC. In a significant number of cases, clinical symptoms post-transfusion are reported by the clinician, yet the BCs from the patient and/or PC are negative. The topic of 'missed bacterial detection' has therefore been the focus of several primary research studies and review articles, suggesting that biofilm formation in the blood bag and the presence of viable but non-culturable (VBNC) pathogens are the major causes of this missed detection. However, platelets are emerging as key players in early host responses to infection and as such, the aforementioned biofilm formation could elicit 'platelet priming', which could lead to significant immunological reactions in the host, in the absence of planktonic bacteria in the host bloodstream. This review reflects on what is known about missed detection and relates this to the emerging understanding of the effect of bacterial contamination on the platelets themselves and the significant role played by platelets in exacerbation of an immune response to infection within the transfusion setting.